Posterior Lumbar Plexus Block: Anatomy, Approaches, and Techniques. Issue 2 (1st March 2005) - Awad, Imad T.; Duggan, Edel M.
Abstract : Lumbar plexus is an effective but underused regional technique that was described nearly 3 decades ago. The original description has been modified several times based on advances in technology, localization, and imaging techniques. This review provides an overview of the history, anatomy, and techniques described to perform this block.